Answer:
For a ) y = 6x - 3
[tex]slope = m = 6\\y-intercept = c = -3\\[/tex]
For b ) y = -2x - 10
[tex]slope = m = -2\\y-intercept = c = -10\\[/tex]
For c ) y = -4x + 4
[tex]slope = m = -4\\y-intercept = c = 4\\[/tex]
Step-by-step explanation:
Given:
a. y = 6x - 3
b. y = -2 (x + 5)
y = -2x - 10
c. y = 4 (-x + 1)
y = -4x + 4
To Find:
y-intercept and the slope for each equation = ?
Solution:
Slope-intercept Formula is given by
[tex]y=mx+c[/tex]
Where,
m = slope
c = y-intercept
So on comparing the Given equations with the above Equation we get
For a ) y = 6x - 3
[tex]slope = m = 6\\y-intercept = c = -3\\[/tex]
For b ) y = -2x - 10
[tex]slope = m = -2\\y-intercept = c = -10\\[/tex]
For c ) y = -4x + 4
[tex]slope = m = -4\\y-intercept = c = 4\\[/tex]